Libyan EFL university students’ narrative writing and management of peer feedback in a blog modeled on a fanfiction writing environment - Harb, Fatma Elhadi B. (2017)
This study explored the narrative writing experience of 28 freshmen EFL Libyan university students in a learner blog modeled on online fanfiction writing environment. It examined the impact of blogging on narrative writing quality. It looked at blog functions stimulating writing, management of peer feedback and discussed how peer feedback may contribute to improving writing. The study reported participants’ and their class teacher’s perspectives on the online writing experience. This one-semester study adopted the mixed-method approach. Data were collected through writing test scores, questionnaire responses from students and transcripts of the interview session with the writing class teacher and the students’ posted peer feedback. Descriptive statistics and the Wilcoxon Signed-Ranks Test were used to analyze quantitative results while textual and thematic analyses were used to analyze qualitative data. The findings revealed that narrative writing performance did not significantly improve after the blog use. The findings also indicated that technological and social functions moderately stimulated writing. Task-Related Feedback was higher than Non-Task Related Feedback, but students’ writing activity on the blog lacked constructive feedback. Most participants preferred teacher feedback and developed subject-related and non-subject related skills due to of their participation on the blog. The study suggests that EFL writing teachers need to understand the environment, which stimulates students’ writing improvement. The study also reemphasizes the importance of a real audience, socialization and a balance of teacher feedback and peer feedback as proposed in constructivism and connectivism.